Deciphering the state of immune silence in fatal COVID-19 patients - Pierre Bost (Nature Portfolio, 2021)
Integrated studies of matched tissue sites and cell types in COVID-19 patients are important to define the immune mechanisms of pathology. Here, the authors describe an immune signature in fatal COVID-19 patients harmonizing single-cell RNA sequencing of blood and matched BAL cells with deep clinical, immunological and functional data.